The Effects of Vocational Training Programmes on the Duration of Unemployment in Eastern Germany - Reinhard Hujer; Stephan L. Thomsen; Christopher Zeiss (Institute for the Study of Labor (IZA), 2004)
This paper focuses on the effects of vocational training programmes on the duration of unemployment in Eastern Germany. We use information from administrative data of the Federal Employment Office. To allow for observable and possible unobservable influences we apply a multivariate mixed proportional hazard model. Furthermore, particular interest is spent on possible locking-in effects by separate estimation of in- and after-programme effects. Regarding several different programme durations our results show insignificant in- and after-programme effects for short-term programmes, insignificant in-programme and negative after-programme effects for mid-term programmes and negative in- and afterprogramme effects for long-term programmes.
Keywords: J68; J64; I28; J24; 330; vocational training; programme evaluation; duration analysis; treatment effect; Arbeitsmarktpolitik; Berufsbildung; Wirtschaftspolitische Wirkungsanalyse; Arbeitslosigkeit; Dauer; Schätzung; Neue Bundesländer; treatment effect